Design and Psychometric Assessment of the Meaning in Life Questionnaire in Iranian Patients With Spinal Cord Injuries - Mohammad Ali Cheraghi; Fatemeh Bahramnezhad; Mitra Zolfaghari; Parvaneh Asgari; Fatemeh Keshmiri (Iran University of Medical Sciences, 2017)
Background: Without the meaning in life and setting goals, the life will be full of pain and suffering. Hence, psychologists try to discover patient's meaning in life and guiding it. A good questionnaire is very important to identify and measure meaning in life. Therefore, the present study focused on design and psychometric assessment of meaning in life questionnaire in patients with SCI. Methods: A total of 258 patients with spinal cord injury in 2014-2016 were selected using the available sampling method. Waltz (2010) method was used for designing the questionnaire: 1) a copy of the questionnaire was designed based on the literature review, 2) face and content validity confirmation of the questionnaire by 10 experts, 3) exploratory factor analysis for construct validity was done, and 4) internal consistency of the questionnaire was confirmed by Cronbach's alpha coefficient. The SPSS version 16 software was used for analyzing the data. Results: Estimation of CVR and CVI revealed the content validity to be 0.81 and 0.9, respectively. Finally, the questionnaire was extracted with 38 items based on 4 factors: the first factor (positive perception) with 13 items, the second factor (sense of meaning) with 9 items, the third factor (purposefulness) with 7 items, and the fourth factor (spirituality) with 9 items. Conclusion: Considering the existence of a valid and reliable questionnaire, it is recommended that studies be conducted on the meaning of life in various diseases and should be designed to support these patients.